Characterisation of the permanent solar wind impact on the high-latitude electron density - Borries, Claudia; Iochem, Pelin; Tasnim, Samira (2023)
It is well known, that energy transmitted from the solar wind in the geosystem drives numerous electrodynamic processes in the high latitude thermosphere and ionosphere, most prominent plasma convection, ion-driven winds and Joule heating. Especially during storm conditions, when the solar wind energy input becomes extreme, these processes become very intense and impact the global thermosphere-ionosphere system. Although the solar wind impact on the high-latitude ionosphere is obvious, no correlation studies between changes in the solar wind conditions and changes in the ionosphere electron density has been published. In this study, we are presenting correlation results for Tromso location, which show both positive and negative correlation between both parameters depending on solar cycle, season and local time. This knowledge about the complex ionosphere response characteristics to solar wind conditions is essential for the development of appropriate high-latitude electron density models.